A multiscale analysis in CD38−/− mice unveils major prefrontal cortex dysfunctions. Issue 5 (7th March 2019) - Martucci, Lora L.; Amar, Muriel; Chaussenot, Remi; Benet, Gabriel; Bauer, Oscar; De Zélicourt, Antoine; Nosjean, Anne; Launay, Jean‐Marie; Callebert, Jacques; Sebrié, Catherine; Galione, Antony; Edeline, Jean‐Marc; et al.
ABSTRACT: Autism spectrum disorder (ASD) is characterized by early onset of behavioral and cognitive alterations. Low plasma levels of oxytocin (OT) have also been found in ASD patients; recently, a critical role for the enzyme CD38 in the regulation of OT release was demonstrated. CD38 is important in regulating several Ca 2+ ‐dependent pathways, but beyond its role in regulating OT secretion, it is not known whether a deficit in CD38 expression leads to functional modifications of the prefrontal cortex (PFC), a structure involved in social behavior. Here, we report that CD38 −/− male mice show an abnormal cortex development, an excitation‐inhibition balance shifted toward a higher excitation, and impaired synaptic plasticity in the PFC such as those observed in various mouse models of ASD. We also show that a lack of CD38 alters social behavior and emotional responses. Finally, examining neuromodulators known to control behavioral flexibility, we found elevated monoamine levels in the PFC of CD38 −/− adult mice. Overall, our study unveiled major changes in PFC physiologic mechanisms and provides new evidence that the CD38 −/− mouse could be a relevant model to study pathophysiological brain mechanisms of mental disorders such as ASD.—Martucci, L. L., Amar, M., Chaussenot, R., Benet, G., Bauer, O., de Zélicourt, A., Nosjean, A., Launay, J.‐M., Callebert, J., Sebrié, C., Galione, A., Edeline, J.‐M., de la Porte, S., Fossier, P., Granon, S., Vaillend, C., Cancela, J.‐M., A multiscale analysis in CD38 ‐/‐ mice unveils major prefrontal cortex dysfunctions. FASEB J. 33, 5823–5835 (2019). www.fasebj.org